A volumetric absorptive microsampling LC–MS/MS method for five immunosuppressants and their hematocrit effects. (20th March 2019) - Koster, Remco A; Niemeijer, Pascal; Veenhof, Herman; Hateren, Kai van; Alffenaar, Jan-Willem C; Touw, Daan J
Aim: The aim of this study was to develop and validate a LC–MS/MS assay for tacrolimus, sirolimus, everolimus, cyclosporin A and mycophenolic acid using volumetric absorptive microsampling tips as a sampling device and to investigate the effect on the recoveries of the analyte concentration in combination with the hematocrit (HT), which included temsirolimus (a structural analog).Results: The maximum observed overall bias was 9.6% for the sirolimus LLOQ, while the maximum overall coefficient of variation was 8.3% for the everolimus LLOQ. All five immunosuppressants demonstrated to be stable in the volumetic absorbtive microsampling tips for at least 14 days at 25°C. Biases caused by HT effects were within 15% for all immunosuppressants between HT levels of 0.20 and 0.60 l/l, except for cyclosporin A, which was valid between 0.27 and 0.60 l/l. Reduced recoveries were observed at high analyte concentrations in combination with low HT values for sirolimus, everolimus and temsirolimus.Conclusion: A robust extraction and analysis method in volumetric absorptive microsampling tips was developed and fully validated. HT- and concentration-related recovery effects were observed but were within requirements of the purpose of the analytical method.